2015
DOI: 10.1007/s00221-015-4240-x
|View full text |Cite
|
Sign up to set email alerts
|

Neck muscle fatigue alters upper limb proprioception

Abstract: Limb proprioception is an awareness by the central nervous system (CNS) of the location of a limb in three-dimensional space and is essential for movement and postural control. The CNS uses the position of the head and neck when interpreting the position of the upper limb, and altered input from neck muscles may affect the sensory inputs to the CNS and consequently may impair the awareness of upper limb joint position. The purpose of this study was to determine whether fatigue of the cervical extensors muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 49 publications
(73 reference statements)
2
49
0
2
Order By: Relevance
“…Finally, extensive evidence has demonstrated that fatigue results in significant joint position sense impairment (Carpenter et al, 1998;Pedersen et al, 1999;Björklund et al, 2003;Roberts et al, 2003). This impairment arises from numerous factors, including, but not limited to, decreased discharge rate of muscle spindles (Macefield et al, 1991), decreased activity of golgi tendon organs (Hutton and Nelson, 1986), and alterations in central pathways (Sharpe and Miles, 1993;Zabihhosseinian et al, 2015). The extent to which co-contraction and proprioception may have influenced the findings of the present study is unclear, and future investigations quantifying these measures at the forearm would add valuable insight.…”
Section: Performance Fatigability and Hand Trackingmentioning
confidence: 74%
“…Finally, extensive evidence has demonstrated that fatigue results in significant joint position sense impairment (Carpenter et al, 1998;Pedersen et al, 1999;Björklund et al, 2003;Roberts et al, 2003). This impairment arises from numerous factors, including, but not limited to, decreased discharge rate of muscle spindles (Macefield et al, 1991), decreased activity of golgi tendon organs (Hutton and Nelson, 1986), and alterations in central pathways (Sharpe and Miles, 1993;Zabihhosseinian et al, 2015). The extent to which co-contraction and proprioception may have influenced the findings of the present study is unclear, and future investigations quantifying these measures at the forearm would add valuable insight.…”
Section: Performance Fatigability and Hand Trackingmentioning
confidence: 74%
“…Proprioception was tested first when the subject were at rest and then after they exercised on an isokinetic test machine until they were fatigued and it was finally reported that fatigue cause a decrease in the proprioceptive sense. Zabihhosseinian et. al (2015) believe that upper extremity proprioception may deteriorate after fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Using a submaximal dynamic fatigue protocol and a joint positioning task, proprioception was altered in the upper extremity as observed through changes and variability in end-point position (Vafadar et al, 2012). Even more proximal fatigue, such as at the cervical extensors, showed decrements in joint position sense and proprioception in the upper limb (Zabihhosseinian et al, 2015). Similar work using the WristBot and a fatiguing protocol showed decrements in proprioceptive ability after a fatiguing task at the wrist (Mugnosso et al, 2019).…”
Section: The Effects Of Performance Fatigability On Tracking Metricsmentioning
confidence: 95%